Pengaruh Job-Engagement Terhadap Perilaku Withdrawal Melalui Komitmen Organisasi - Alkusani, Alkusani; Sukaris, Sukaris (Jurnal Riset Entrepreneurship, 2019)
Human resources (HR) as one of the keys for the company in achieving its goals and success. Achieving company goals if HR shows good reliability, therefore companies need to make HR play a key role in an organization so that there is involvement, love or employee engagement that impacts on the sustainability of an organization, which can build organizational commitment and also determine how employees will behave. In this study offers a new theoretical framework of management as a shaping factor for the importance of organizational commitment and also the behavior of withdrawal of employees, the sample is carried out on employees with a contractual status of 54 in a higher education institution. The analysis tool uses path analysis with warpPLS. The results show that job engagement negatively influences employee organizational commitment, job engagement has a negative influence on withdrawal behavior, organizational commitment has a negative influence on withdrawal behavior while organizational commitment cannot be a mediating variable between job engagement and employee withdrawal behavior .